2021
DOI: 10.13189/cea.2021.090533
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Semi-empirical Models for the Prediction of Swelling Stress for Compacted Unsaturated Expansive Soils

Abstract: Unsaturated swelling soil behaviour is governed by the matric suction, thus the predetermination of swelling stress for expansive unsaturated soil requires rigorous procedures. However, some swelling stress equations assume full saturation of the soil, which leads to the over-design of infrastructure. This study focused on the validation of predictive swelling stress models that correlate suction with other soil properties. Three models were developed, and independent data were used for the validation of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…To mathematically model grey wolf hunting behaviour 77 , the first three optimal solutions are preserved, while ω are required to relocate by Eqs. (14) to (20). www.nature.com/scientificreports/…”
Section: − → a Andmentioning
confidence: 99%
See 1 more Smart Citation
“…To mathematically model grey wolf hunting behaviour 77 , the first three optimal solutions are preserved, while ω are required to relocate by Eqs. (14) to (20). www.nature.com/scientificreports/…”
Section: − → a Andmentioning
confidence: 99%
“…Several direct and indirect techniques are available to predict the P s -ES such that the latter methods are based on experimental results and engineering judgement. Furthermore, Du et al 12 and Yin et al 13 suggested that to characterize the P s under various conditions, numerous predictive models have been developed, such as Gouy–Chapman diffused double layer models, heat-driven/energy-related models, and data-driven/hybrid models are the three types of existent models 14 . Secondly, the unconfined compressive strength of ES ( UCS -ES) is a desideratum for various parameters used in road design, primarily for highway construction 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…This is because expansive subgrades constitute largely swelling clay minerals, that is, smectite, bentonite, montmorillonite, beidellite, vermiculite, attapulgite, nontronite, and chlorite, which are capable of causing massive volumetric movements upon the slightest moisture infiltration. However, these expansive clay minerals trigger surface rutting and fatigue cracking in pavement structures, which seriously affect their performance and lifespan of pavement structures [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%